2017
DOI: 10.1002/hep.29230
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of astrocyte elevated gene‐1 (AEG‐1) in regulating nonalcoholic steatohepatitis (NASH)

Abstract: Nonalcoholic steatohepatitis (NASH) is the most prevalent cause of chronic liver disease in the Western world. However, an optimum therapy for NASH is yet to be established mandating more in-depth investigation into the molecular pathogenesis of NASH to identify novel regulatory molecules and develop targeted therapies. Here, we unravel a unique function of Astrocyte elevated gene-1/Metadherin (AEG-1/MTDH) in NASH using a transgenic mouse with hepatocyte-specific overexpression of AEG-1 (Alb/AEG-1) and a condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 41 publications
0
55
0
Order By: Relevance
“…Our extensive studies over the last decade have firmly established that Astrocyte elevated gene-1 (AEG-1)/metadehrin (MTDH) functions as a major oncogene for HCC and is highly overexpressed in HCC patients of diverse etiologies by multiple mechanisms including genomic amplification (1222). AEG-1 knockout mice (AEG-1−/−) exhibit complete resistance to N-nitrosodiethylamine (DEN) and phenobarbital (PB)-induced HCC (20).…”
Section: Introductionmentioning
confidence: 99%
“…Our extensive studies over the last decade have firmly established that Astrocyte elevated gene-1 (AEG-1)/metadehrin (MTDH) functions as a major oncogene for HCC and is highly overexpressed in HCC patients of diverse etiologies by multiple mechanisms including genomic amplification (1222). AEG-1 knockout mice (AEG-1−/−) exhibit complete resistance to N-nitrosodiethylamine (DEN) and phenobarbital (PB)-induced HCC (20).…”
Section: Introductionmentioning
confidence: 99%
“…The development of NAFLD is strongly related to hepatic steatosis, due to the rate of fatty acid input ( de novo fatty acid synthesis) exceeds the rate of fatty acid output (fatty acid oxidation) (Goedeke et al, 2018). Therefore, the simultaneous effective suppression of de novo fatty acid synthesis and stimulation of fatty acid oxidation offers an attractive therapeutic strategy for NAFLD (Srivastava et al, 2017). The current study presents the first attempt to demonstrate the following.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating research has demonstrated that imbalanced fatty acid metabolism plays a crucial initial role in the onset and perpetuation of hepatic steatosis (Fabbrini, Sullivan, & Klein, 2010). Imbalanced fatty acid metabolism is characterized by increased de novo fatty acid synthesis and decreased fatty acid oxidation, which subsequently lead to excessive lipid accumulation and steatosis (Goedeke et al, 2018; Srivastava et al, 2017). Thus the identification of a potential target to attenuate fatty acid metabolism disorder may provide the basis for novel therapeutic strategies to alleviate NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…NASH livers are more injured than livers with isolated steatosis, which more likely leads to progressive fibrosis and eventual liver-associated illness and death (3). The molecular players that modulate disease pathogenesis are starting to be identified, enabling translation of research findings to clinical trials (4,5). However, no optimum therapy is yet available, suggesting that a more comprehensive understanding of the onset and progression of NAFLD is needed.…”
mentioning
confidence: 99%
“…The shift from isolated steatosis to NASH is defined histologically as emergence of liver inflammation and hepatocellular injury. The most common theory explaining this shift is the "double-hit hypothesis" (3,5,6). The first hit consists mainly of lipid accumulation, whereas the second comprises sequential innate immune responses (6)(7)(8).…”
mentioning
confidence: 99%